GLOBAL POSTURE REEDUCATION (GPR) TECHNIQUE ON SPORTSMEN AND ANALYSIS OF THE RESULTING SPIROMETRIC DATA (Cuestiones de Fisioterapia, 2012)
Introduction: in the human body there are various families of muscle fibers, slow oxidative or red muscle fibers, fast oxidative glycolytic fibers and fast glycolytic fibers. We will fundamentally concentrate on the red muscle fibers, the static fibers. Global Posture Reeducation (GPR) is a global manual treatment method which utilizes active postures in eccentric isotonic decoaptation to progressively stretch static muscle. Objective: to determine, via Spirometrics tests on each sportsman, the effect that stretching the anterior inspiratory chain with GPR produces on the values of these variables: FVC, FEV1, FEV1/FVC, PImax and PEmax. Material and method: randomized controlled trial, double-blinded, that includes 44 healthy subjects, 4 of which abandoned during the course of the study without justification, leaving a total of 5 women and 35 men, all of which are federated sportsmen in different sports ranging from athletics, soccer, triathlon and water polo from the province of Alicante. The subjects are randomly assigned to one of two possible groups: case study group or control study group; both groups continue with their training regime, but GPR treatment will be applied on the study group and not on the control group. All subjects participated in a forced spirometry test, maximum inspiratory pressure test and a maximum expiratory pressure test, all completed at the beginning and the end of the study, conducted at the University Miguel Hernández de Elche. Exclusion criteria: suffering from degenerative diseases, respiratory, dermatological, cardiovascular diseases or pregnancy. Results: the obtained results don’t show significant improvements in any of the analyzed parameters. Conclusion: the GPR technique used to increase analyzed pulmonary parameters on sports subjects isn’t effective with the experimental process carried out and the subject group selected.